Ethical challenges of embryo donation in embryo donors and recipients - Mahboubeh Taebi; Reyhane Bahrami; Narges Bagheri-Lankarani; Mohsen Shahriari (Wolters Kluwer Medknow Publications, 2018)
Background: Embryo donation, as one of the novel assisted reproductive technologies (ART), has remained a controversial issue. This is due to this methods' need for individuals from outside the family circle. Their presence can cause many ethical issues and complicate the designing and planning of the embryo donation process. The present study was conducted with the aim to assess the ethical challenges of embryo donation from the view point of embryo donors and recipients. Material and Methods: This descriptive, cross-sectional study was conducted on 192 couples (96 embryo donators and 96 embryo recipients) referring to Isfahan Fertility and Infertility Center and Royan Institute, Iran. The subjects were selected through convenience sampling. The data collection tool was the researcher-made Ethical Challenges Questionnaire. Data were analyzed in SPSS software. Results: Embryo donors and recipients expresses the most important ethical challenges of embryo donation in the principle of justice (70.20%) and respect for autonomy (42.57%), respectively. Conclusions: The four ethical principles are important in the view of embryo donors and recipients; however, they highlighted the importance of the principle of respect for autonomy considering the existing barriers in the services of infertility centers. Legislators and relevant authorities must take measures toward the development of guidelines for this treatment method in the framework of ethics principles and incorporate all four principles independently.